A Boolean Networks Approach to Modeling and Resilience Analysis of Interdependent Critical Infrastructures. (14th July 2018) - Galbusera, Luca; Giannopoulos, Georgios; Argyroudis, Sotiris; Kakderi, Kalliopi
Abstract: In this article, we propose a dynamic Boolean network‐type mathematical representation of networked critical infrastructures under stress. Our formulation is obtained as a threshold‐based approximation of a discrete‐time switched system meant to describe failure and recovery phases that may span considerably different time periods. The formalism can incorporate mitigating factors, resource constraints, and allocation strategies affecting the response of the system and the unfolding of restoration processes. As such, the tool may inform both contingency planning and consequence assessment. We also discuss an illustrative case study concerning the recovery process of selected infrastructures of the Thessaloniki Port in an earthquake scenario. Simulations are performed for assigned parameter distributions associated with the different operational modes. Finally, a performance loss indicator is computed to assess the overall service perturbation affecting the system. For the needs of this analysis, fragility curves have been selected from the literature, whereas restoration curves, recovery priorities, classification of components, and other modeling variables have been defined in collaboration with the local Port Authority.